Positive electrode active material, preparation method, positive electrode, rechargeable lithium battery, and all-solid-state rechargeable battery

By using the lithium-rich manganese positive electrode active material mixed with solid solution phase and composite phase in Chemical Formula 1, the problems of voltage drop and energy density reduction in the prior art are solved, and the effects of high capacity, long cycle life and high energy density are achieved.

CN119725517APending Publication Date: 2025-03-28SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411358231.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing lithium-rich manganese positive electrode active substances have problems of voltage drop and energy density reduction during charging and discharging, and the cycle life characteristics are poor.

Method used

A compound represented by Chemical Formula 1 is used as the positive electrode active material, which includes a mixture of solid solution phase and a composite phase, and the voltage drop and energy density are improved by controlling the capacity ratio of O-redox expression.

Benefits of technology

The high discharge capacity and average discharge voltage are improved, while the high-temperature cycle life characteristics and energy density are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725517A_ABST
    Figure CN119725517A_ABST
Patent Text Reader

Abstract

The present application provides a positive electrode active material for a rechargeable lithium battery, a method of preparing the same, a positive electrode including the same, a rechargeable lithium battery, and an all-solid-state rechargeable battery. The positive electrode active material for a rechargeable lithium battery includes a compound represented by Chemical Formula 1. In Chemical Formula 1, 0 < a < 1, 0.03 < = x < = 0.2, 0.35 < = y < = 0.7, 0 < b < 1, 0 < c < 1, and 0.5 < = z < = 1.0. [Chemical Formula 1] a [Li1 + x (NiyMn1-y) 1-xO2] + (1-a) [b (LiNizMn1-zO2) + c (Li2MnO3)].
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Disclosed herein are a positive electrode active material, a method for preparing the same, a positive electrode including the same, a rechargeable lithium battery, and an all-solid-state rechargeable battery. Background Art

[0002] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) or electric vehicles have used rechargeable lithium batteries with high energy density and easy portability as driving power sources. Recently, research has been actively conducted to use rechargeable lithium batteries with high energy density as driving power sources and / or power storage power sources for hybrid or electric vehicles.

[0003] Various positive electrode active materials have been studied to realize rechargeable lithium batteries for various appropriate purposes. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and lithium cobalt oxides are mainly used as positive electrode active materials. However, although the demand for rechargeable lithium batteries with large size, high capacity and / or high energy density has increased rapidly recently, the supply of transition metals (such as nickel, cobalt, etc.) may not only be seriously insufficient, but also its price has increased sharply. Accordingly, it is necessary to develop low-cost and high-energy positive electrode active materials.

[0004] Lithium-manganese-rich (LMR) materials have attracted attention as an ultra-low-cost generation of positive electrode active materials, which are layered positive electrode active materials that include excess lithium and a relatively large amount of manganese and have a layered structure, and thus exhibit high capacity by applying a new principle called oxygen redox (O-redox) and existing transition metal redox, and at the same time (e.g., synchronously) include low-cost manganese in a high proportion.

[0005] However, since the LMR material itself has low O-redox reversibility (which is the main source that can generate high capacity) and can release oxygen during charging and discharging, thereby deteriorating its crystal structure, there may be a voltage decay phenomenon due to the voltage drop during charging and discharging. In addition, since the capacity expressed by O-redox in the total capacity is high, the average discharge voltage of the positive electrode may be low. Accordingly, although O-redox is the main source of high capacity, when its ratio is too high, there is a problem of deterioration of cycle life characteristics or energy density calculated as (capacity×voltage). Summary of the invention

[0006] The present application provides a cost-competitive lithium-manganese-rich positive electrode active material that ensures high capacity characteristics due to O-redox while minimizing or reducing the side effects caused by O-redox, thereby minimizing or reducing voltage drop and energy density reduction and improving cycle life characteristics.

[0007] Some embodiments provide a positive electrode active material for a rechargeable lithium battery, including a compound represented by Chemical Formula 1.

[0008] Chemical formula 1

[0009] a[Li 1+x (Ni y Mn 1-y ) 1-x O2]+(1-a)[b(LiNi z Mn 1-z O2)+c(Li2MnO3)]

[0010] In Chemical Formula 1, 0<a<1, 0.03≤x≤0.2, 0.35≤y≤0.7, 0<b<1, 0<c<1, and 0.5≤z≤1.

[0011] Some embodiments provide a method of preparing a positive electrode active material. Some embodiments provide a positive electrode for a rechargeable lithium battery including the positive electrode active material.

[0012] Some embodiments provide a rechargeable lithium battery including a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte.

[0013] Some embodiments provide an all-solid-state rechargeable battery including a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode.

[0014] According to some embodiments, the positive electrode active material is a lithium-manganese-rich positive electrode active material with high price competitiveness, which can achieve high capacity by utilizing O-redox, and at the same time effectively improve the problems of voltage drop and energy density by controlling the ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material to show high discharge capacity and average discharge voltage, and can achieve excellent high temperature cycle life characteristics and high energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The accompanying drawings, together with the specification, illustrate embodiments of the presently disclosed subject matter, and, together with the description, serve to explain principles of embodiments of the presently disclosed subject matter.

[0016] Figure 1 is a perspective view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0017] Figure 2 is a cross-sectional view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0018] Figure 3 and Figure 4 is a perspective view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0019] Figure 5 A graph showing a peak in the (003) plane and a peak in the (020) plane as a result of X-ray diffraction analysis (XRD) of the positive electrode active materials of Example 2 (950°C), Example 5 (700°C) and Comparative Example 5 (500°C).

[0020] Figure 6 3 is a scanning electron microscope (SEM) image of the particle surface of the positive electrode active material prepared in Example 2.

[0021] Figure 7 This is a SEM image of the particle surface of the positive electrode active material prepared in Example 5.

[0022] Figure 8 is a SEM image of the particle surface of the positive electrode active material prepared in Comparative Example 5.

[0023] Description of Reference Numerals

[0024] 100: Rechargeable lithium battery 10: Positive electrode

[0025] 11: Positive electrode lead lug 12: Positive electrode terminal

[0026] 20: Negative electrode 21: Negative electrode lead lug

[0027] 22: Negative electrode terminal 30: Separator

[0028] 40: electrode assembly 50: shell

[0029] 60: Sealing member 70: Electrode terminal piece

[0030] 71: Positive electrode terminal tab 72: Negative electrode terminal tab DETAILED DESCRIPTION

[0031] Hereinafter, example embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the subject matter of the present disclosure may be embodied in many different forms and should not be construed as limited to the example embodiments set forth herein.

[0032] The terms used herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly dictates otherwise, a singular expression includes a plural expression.

[0033] As used herein, "combinations thereof" means mixtures, laminates, composites, copolymers, alloys, blends, reaction products, etc. of the components.

[0034] In this document, it should be understood that terms such as "comprising", "including" or "having" are intended to indicate the presence of embodied features, quantities, steps, elements or combinations thereof, but do not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements or combinations thereof.

[0035] In the drawings, the thickness of layers, films, panels, regions, etc. may be exaggerated for clarity, and the same reference numerals denote the same elements throughout the specification. It will be understood that when an element (such as a layer, film, region, or substrate) is referred to as being "on" another element, it can be directly on the other element, or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements.

[0036] In the present disclosure, the “layer” herein includes not only a shape formed on the entire surface when viewed from a plan view but also a shape formed on a partial surface.

[0037] In the present disclosure, the average particle size can be measured by any suitable method commonly used in the art, and for example, can be measured by a particle size analyzer, and / or can be measured by a transmission electron microscope image and / or a scanning electron microscope image. In some embodiments, the average particle size value can be obtained by using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. As used herein, when no definition is otherwise provided, the average particle size (D 50 ) means the diameter of a particle having a cumulative volume of 50 volume % in a particle size distribution obtained by randomly measuring the size (diameter or length of the major axis) of about 20 particles in a scanning electron microscope image.

[0038] In this document, "or" is not interpreted as an exclusive meaning. For example, "A or B" is interpreted to include A, B, A+B, etc.

[0039] The term “metal” is interpreted as a concept including common metals, transition metals, and metalloids (semimetals).

[0040] Positive electrode active material

[0041] Some embodiments provide a positive electrode active material for a rechargeable lithium battery, including a compound represented by Chemical Formula 1.

[0042] Chemical formula 1

[0043] a[Li 1+x (Niy Mn 1-y ) 1-x O2]+(1-a)[b(LiNi z Mn 1-z O2)+c(Li2MnO3)]

[0044] In Chemical Formula 1, 0<a<1, 0.03≤x≤0.2, 0.35≤y≤0.7, 0<b<1, 0<c<1, and 0.5≤z≤1.0.

[0045] In Chemical Formula 1, [Li 1+x (Ni y Mn 1-y ) 1-x O2] indicates a solid solution phase and [b(LiNi z Mn 1-z O2) + c (Li2MnO3)] indicates a composite phase. In some embodiments, the compound represented by Chemical Formula 1 includes both a solid solution phase and a composite phase. Existing lithium-rich manganese materials may generally have a solid solution phase or a composite phase structure. In an embodiment of the present disclosure, the positive electrode active material according to some embodiments may be a material to which not only a composite phase but also a solid solution phase is added, for example, a material in which a composite phase and a solid solution phase are mixed together, or a material in which a composite phase and a solid solution phase compete (for example, a heterogeneous phase) and coexist.

[0046] Herein, according to some embodiments of the present disclosure, a solid solution phase is a solid mixture in which different elements are completely and evenly mixed together. A solid solution phase may mean that other elements are mixed into a solid crystal and are evenly distributed, showing the appearance of a solution in which a solute is evenly distributed in a solvent. A solid solution phase may be in the form of a continuous quasi-isostructural compound having new properties due to the close relationship between two or more individual components. A solid solution phase is homogeneous, has almost the same composition, and may have a single phase or single crystal structure. In contrast, a composite phase is composed of two or more combined materials, and may be composed of materials with different physical properties, and these materials retain physical differences. A composite phase may be heterogeneous and include two or more compositions and two or more phases or crystal structures.

[0047] The presence of the solid solution phase and the composite phase can be confirmed by energy above hull analysis and / or X-ray diffraction (XRD) diffraction peaks as further described below.

[0048] In Chemical Formula 1, a is the ratio (or coefficient) of the solid solution phase and (1-a) is the ratio (or coefficient) of the composite phase. In Chemical Formula 1, a ranges from 0<a<1, for example, 0.1≤a≤0.9, 0.2≤a≤0.8, or 0.3≤a≤0.7, but the range is not particularly limited.

[0049] In Formula 1, y is the nickel content of the solid solution phase and z represents the nickel content of the layered material in the composite phase. The range of y may be 0.35≤y≤0.7, for example, 0.35≤y≤0.66, 0.4≤y≤0.60, 0.45≤y≤0.55, or 0.5≤y≤0.66. The range of z may be 0.5≤z≤1.0, for example, 0.5≤z≤0.99, 0.5≤z≤0.95, 0.50≤z≤0.85, or 0.6≤z≤0.75.

[0050] The positive electrode active material according to some embodiments may be a lithium-rich manganese material having the following nickel content: about 50 mol% to about 70 mol% or, for example, about 50 mol% to about 66 mol% based on 100 mol% of all metals excluding lithium. The positive electrode active material of this composition can ensure price competitiveness by excluding or only containing a very small amount of expensive cobalt and also containing low-cost manganese, can achieve high capacity by ensuring capacity according to the nickel content, and can simultaneously ensure the capacity expressed by O-redox, and effectively improve the problems of voltage drop and low energy density by limiting the ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material.

[0051] In Chemical Formula 1, x is related to the lithium content, and (1+x) corresponds to the molar ratio of lithium. The range of x is 0.03≤x≤0.2, for example, 0.05≤x≤0.15, 0.03≤x≤0.15, 0.03≤x≤0.13, 0.03≤x≤0.11 or 0.03≤x≤0.09. For example, the ratio of the lithium content (1+x) to the total content of metals excluding lithium (1-x), for example, (1+x) / (1-x) may be about 1.06 to about 1.5, about 1.06 to about 1.3 or about 1.1 to about 1.2.

[0052] In Chemical Formula 1, b and c can be respectively z Mn 1-z The ratio of (O2) and (Li2MnO3) is related and can be 0<b<1, 0<c<1, for example, 0.1≤b≤0.9, 0.2≤b≤0.8 or 0.3≤b≤0.7, and 0.1≤c≤0.9, 0.2≤c≤0.8 or 0.3≤c≤0.7, but the range is not particularly limited.

[0053] The positive electrode active material according to some embodiments may have an "on-shell energy" of less than about 25meV / atom. The on-shell energy refers to the difference between the formation energy of the composite phase in the most stable state and the formation energy of the solid solution phase in the metastable state. 25meV / atom is the energy that an atom can overcome at room temperature (300K), which indicates the thermodynamic stability of the material at room temperature. The larger the on-shell energy, the lower the possibility or proportion of existence as a solid solution phase and the higher the possibility or proportion of existence as a stable composite phase. The positive electrode active material according to some embodiments may satisfy an on-shell energy of less than about 25meV / atom, and therefore, the composite phase and the solid solution phase may exist simultaneously (e.g., synchronously) at room temperature.

[0054] In this way, compared with the existing composite phase lithium-rich manganese materials, the positive electrode active material according to some embodiments including a solid solution phase can contain oxygen in the structure in a relatively more stable manner. In the existing composite phase lithium-rich manganese materials (a=0), during the charge and discharge process, due to the LiNi z Mn 1-z O2 phase and Li2MnO3 phase different lattice constant and lithium concentration cause stress at the interface, thus oxygen vacancies occur. Although the present disclosure is not limited by any particular mechanism or theory, it is believed that this is because in the positive electrode active material according to some embodiments, the amount of the interface is reduced, thereby reducing the probability of problems occurring at the interface. Accordingly, there are fewer structural changes due to oxygen vacancies during the charging and discharging process, and the voltage drop problem caused by oxygen generation and structural degradation can be effectively improved. Ultimately, in some embodiments, by solving the problem of voltage drop caused by charging and discharging while using a lithium-rich manganese material with high capacity and high price competitiveness, a positive electrode active material with improved cycle life characteristics and energy density can be provided.

[0055] In the positive electrode active material according to some embodiments, the capacity expressed by O-redox is determined by Li 1+x (Ni y Mn 1-y ) 1-x O2 and / or Li2MnO3 in composite phase. 1+x (Ni y Mn 1-y ) 1-x Either or both of O2 and Li2MnO3 can contribute to the O-redox.

[0056] According to some embodiments, the positive electrode active material may have a composition that utilizes O-redox but minimizes or reduces the side effects caused by O-redox. For example, the capacity expressed by O-redox accounts for 100% of the total capacity of the positive electrode active material may be less than about 15%, for example, about 1% to about 9.9% or about 3% to about 9.5%. As an example, when the capacity expressed by O-redox accounts for 100% of the total capacity of the positive electrode active material in a lithium-rich manganese material with a Ni content of about 50 mol% to about 70 mol% is controlled to be less than about 15%, the problem of voltage drop caused by charging and discharging can be effectively improved, so the cycle life characteristics and energy density can be improved.

[0057] As an example, a method for measuring the ratio of the capacity expressed by O-redox to the total capacity of 100% of the positive electrode active material is as follows. A half-cell is manufactured by using a positive electrode using a corresponding positive electrode active material and a lithium counter electrode and applying a carbonate-based electrolyte, and charging and discharging are performed under the following conditions. After the first setting, the second setting is performed.

[0058] First Setup

[0059] (1) First cycle: Charge to about 4.65 V at 25°C at a constant current of 0.1C, then maintain this voltage until the current value reaches 0.05C, and then discharge to 2.5 V at a constant current of 0.1C.

[0060] (2) Second cycle: Charge to about 4.45 V at 25°C at a constant current of 0.2C, then maintain the voltage until the current value reaches 0.05C, and then discharge to 2.5 V at a constant current of 0.2C.

[0061] Second Setting

[0062] (1) First cycle: Charge to about 4.45 V at 25°C at a constant current of 0.2C, then maintain this voltage until the current value reaches 0.05C, and then discharge to 2.5 V at a constant current of 0.2C.

[0063] (2) Second cycle: Charge to about 4.45 V at 25°C at a constant current of 0.2C, then maintain the voltage until the current value reaches 0.05C, and then discharge to 2.5 V at a constant current of 0.2C.

[0064] When the discharge capacity of the second cycle of the first setting is X and the discharge capacity of the second cycle of the second setting is Y, the XY value may be referred to as the capacity expressed by O-redox. If O-redox is activated by charging to about 4.65V in the first cycle, the capacity increases in the second cycle, and this increase may be regarded as the capacity expressed by O-redox. The ratio (%) of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material may be calculated using Equation 1.

[0065] Equation 1

[0066] {(XY) / X}×100

[0067] Generally, in the first cycle of the positive electrode in which O-redox is represented, it is understood that the O-redox reaction occurs at a high voltage range of greater than or equal to about 4.45V, but the voltage at which the expression level is maximum may be affected by various factors (such as the surface condition or composition of the positive electrode, and the electrolyte composition). However, in this high voltage range, in addition to the O-redox reaction, a side reaction of the electrolyte solution also occurs, wherein the higher the voltage, the more serious the side reaction becomes, and when the voltage is excessively increased, the side reaction occurs more than the O-redox reaction, making it difficult to accurately measure the capacity expressed by the O-redox. When the voltage is excessively reduced in order to reduce the side reaction of the electrolyte solution, the O-redox itself occurs less, also making it difficult to accurately measure the capacity expressed by the O-redox. Accordingly, the inventors have conducted various experiments to set the upper limit voltage of the first cycle of the first setting to about 4.65 V, at which the capacity expressed by O-redox is most effectively measured, but the voltage may be changed by various factors (such as the state or composition of the positive electrode surface, the composition of the electrolyte solution, etc.), for example, in the range of greater than or equal to about 4.55 V and less than or equal to about 4.8 V, for example, about 4.55 V, about 4.6 V, about 4.7 V, about 4.75 V, about 4.8 V, etc.

[0068] Generally speaking, the more O-redox is expressed, the lower the average discharge voltage after O-redox activation, but in the positive electrode active material according to some embodiments, the average discharge voltage can be improved by controlling the proportion of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material. For example, under the second cycle of the first setting, the average discharge voltage can be greater than or equal to about 3.83V (vs.Li / Li+), for example, greater than or equal to about 3.84 V. Herein, when the positive electrode active material is applied to the positive electrode to manufacture a half-cell unit charged and discharged in the aforementioned first setting, the average discharge voltage may mean the average discharge voltage under the second cycle of the first setting applied. The average discharge voltage may be calculated, for example, by dividing the integral of the area under the voltage curve (voltage-capacity curve graph) by the discharge capacity.

[0069] The positive electrode active material according to some embodiments may have a ratio of about 2% (I a / I b ), which is the ratio of the peak intensity of the (020) plane of Li2MnO3 corresponding to the C2 / m space group in X-ray diffraction analysis to the peak intensity of the (020) plane of Li2MnO3 corresponding to the C2 / m space group in X-ray diffraction analysis. Space group LiNi z Mn 1-z O2 ratio of the peak intensity of the (003) plane. In this article, the (003) plane refers to the lattice plane corresponding to the Miller index (003), and the (020) plane refers to the lattice plane corresponding to the Miller index (020). In XRD, the peak of the (003) plane appears near 2θ=18°~19°, and the peak of the (020) plane appears near 2θ=20.3°~22°. The peak of the (020) plane may be a peak due to Li2MnO3 in Chemical Formula 1. Because the positive electrode active material according to some embodiments shows a (020) peak of Li2MnO3 with reduced intensity in the composite phase, the ratio of the peak intensity of the (020) plane to the peak intensity of the (003) plane can be controlled to be less than or equal to about 2%. I a / I b The ratio may be, for example, less than or equal to about 1.9%, less than or equal to about 1.8%, or less than or equal to about 1.0%, for example, about 0.5% to about 2%, about 0.8% to about 1.9%, about 0.3% to about 1.8%, or about 0.3% to about 1.0%. a / I b When the ratio satisfies the range herein, the ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material can be reduced, which can improve the voltage drop problem that otherwise occurs during charge and discharge.

[0070] The positive electrode active material according to some embodiments may have a value greater than or equal to about 1.04 in XRD. For example, greater than or equal to approximately or about ~Approx. For example, the a lattice constant of the positive electrode active material may be greater than or equal to about In some embodiments, the ratio of the c lattice constant to the a lattice constant may be less than or equal to about 4.968, for example, less than or equal to about 4.965, less than or equal to about 4.960, or about 4.955 to about 4.965. When the a lattice constant of the positive electrode active material and the ratio of the c lattice constant to the a lattice constant meet the ranges herein, the voltage drop problem of the rechargeable lithium battery including the same during charging and discharging can be effectively improved, and the cycle life characteristics and energy density can also be improved.

[0071] The positive electrode active material of some embodiments can achieve a higher reversible discharge capacity ratio than existing lithium-rich manganese materials. In this article, in the method of measuring the ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material, the reversible discharge capacity ratio may be the ratio (X / A) of the discharge capacity (X) of the second cycle of the first setting to the charge capacity (A) of the first cycle of the first setting. The reversible discharge capacity ratio may affect the N / P ratio, which is the ratio of the load level between the negative electrode and the positive electrode in the full battery cell design. For example, when the reversible discharge capacity ratio is low, the total energy density becomes lower because a negative electrode with a higher load level should be used in the battery cell to achieve the same positive electrode capacity. For example, a higher reversible discharge capacity ratio may be more advantageous or beneficial for increasing the energy density of a rechargeable lithium battery.

[0072] The positive electrode active material according to some embodiments may have a reversible discharge capacity ratio greater than or equal to about 63% or greater than or equal to about 72%, however, the reversible discharge capacity ratio may be further improved by reducing the molar ratio of lithium to total metal excluding lithium, wherein the reversible discharge capacity ratio may be greater than or equal to about 77% or greater than or equal to about 79%, which may further improve the energy density of the rechargeable lithium battery.

[0073] According to some embodiments, the positive electrode active material can achieve a higher powder compaction density than the existing lithium-rich manganese material. The positive electrode active material may have a powder compaction density greater than about 2.70g / cc, for example, greater than or equal to about 2.71g / cc, greater than or equal to about 2.74g / cc, or about 2.71 to about 2.85g / cc. In this article, the powder compaction density can be measured after the positive electrode active material is pressed into a compact at a pressure of about 3.3 tons. Generally speaking, when the content of lithium and manganese is large, the powder compaction density of the positive electrode active material becomes lower because the proportion of LiMnO2, Li2MnO3, etc. with low theoretical density in the positive electrode active material becomes higher. In some embodiments, the positive electrode active material can achieve a relatively high powder compaction density due to the slightly lower lithium and / or manganese content than the existing lithium-rich manganese material and the low proportion of the phase with a lower theoretical density, thereby expecting to achieve a high electrode density.

[0074] According to some embodiments, the positive electrode active material may have a residual lithium content of less than or equal to about 0.4wt%, for example, less than or equal to about 0.3wt%, less than or equal to about 0.2wt%, less than or equal to about 0.1wt%, or about 0.001wt% to about 0.1wt% on the surface. This can be said to be a feature that is different from high nickel materials with a nickel content greater than about 70mol%.

[0075] The positive electrode active material may be in the form of secondary particles made by aggregating a plurality of primary particles. The average particle size (D 50 ) may be about 1 μm to about 20 μm, for example, about 5 μm to about 15 μm or about 8 μm to about 12 μm. For example, the positive electrode active material may have an average particle size (D 50 ) is about 0.5 μm to about 8 μm and the average particle size (D 50 ) is a mixture of large particles of about 9 μm to about 20 μm. Herein, the average particle size can be obtained by measuring the size (e.g., particle size, major diameter, or length of major axis) of any 20 particles from the SEM image of the positive electrode active material to obtain a particle size distribution, and the particle size with a cumulative volume of 50% by volume in the particle size distribution is regarded as the average particle size (D 50 ).

[0076] Method for preparing positive electrode active material

[0077] Some embodiments provide a method of preparing a positive electrode active material, the method comprising mixing a precursor represented by Chemical Formula 2 and a lithium raw material together and performing a heat treatment. Herein, a molar ratio of lithium of the lithium raw material to the total metal of the precursor is designed to be about 1.06 to about 1.5.

[0078] Chemical formula 2

[0079] Ni y2 Mn 1-y2 (OH)2

[0080] In Chemical Formula 2, 0.5≤y2≤0.7.

[0081] In Formula 2, 0.5≤y2≤0.66, 0.5≤y2≤0.60, or 0.5≤y2≤0.55. In some embodiments, the molar content of nickel in the precursor to the total metal may satisfy about 50 mol% to about 70 mol%, for example, about 50 mol% to about 66 mol%, about 50 mol% to about 60 mol%, or about 50 mol% to about 55 mol%.

[0082] When the positive electrode active material precursor is designed to have the nickel content as above, the positive electrode active material of Chemical Formula 1 can be synthesized, wherein the desired solid solution phase and the composite phase exist simultaneously (e.g., synchronously). When the molar content of nickel in the precursor to the total metal is less than about 50 mol% or greater than about 70 mol% (which may result in an energy on the shell greater than about 25 meV / atom), the solid solution phase and the composite phase may not coexist at room temperature, for example, only the composite phase may exist. In addition, corresponding to Space group LiNi z Mn 1-z O2 may not be formed or formed at a low rate, but Li2MnO3 corresponding to the C2 / m space group may be formed at an increased rate, and accordingly, the peak intensity of the (020) plane (I a ) peak intensity (I b ) ratio, that is, I a / I b Herein, the capacity expressed by O-redox accounts for an increased proportion of 100% of the total capacity of the positive electrode active material, and the voltage drop increases during charge and discharge, thereby deteriorating the cycle life characteristics.

[0083] The molar ratio of lithium of the lithium raw material to the total metal of the precursor (Li / (Ni+Mn)) may be about 1.06 to about 1.5, for example, about 1.06 to about 1.4, about 1.1 to about 1.3, or about 1.1 to about 1.2. When the molar ratio of lithium of the lithium raw material to the total metal of the precursor satisfies the above range, the positive electrode active material according to Chemical Formula 1 can be synthesized in which the solid solution phase and the composite phase exist simultaneously (for example, synchronously).

[0084] The heat treatment may be performed at a temperature range of, for example, about 700°C to about 1100°C, for example, about 700°C to about 1000°C or about 750°C to about 950°C, and may be performed for about 10 hours to about 40 hours, about 12 hours to about 36 hours, or about 20 to about 30 hours.

[0085] The heat treatment may include a temperature increasing step, a temperature holding step, and a temperature reducing step. The temperature increasing rate in the temperature increasing step and the temperature reducing rate in the temperature reducing step may be, for example, about 1°C / min to about 10°C / min or about 2°C / min to about 5°C / min, respectively, and if these ranges are met, it is advantageous or beneficial to effectively synthesize the positive electrode active material according to the desired chemical formula 1.

[0086] Positive electrode

[0087] In some embodiments, a positive electrode for a rechargeable lithium battery including the aforementioned positive electrode active material is provided. The positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, and the positive electrode active material layer may include the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types (or types) of positive electrode active materials, and may optionally further include a binder, a conductive material (e.g., a conductive material) or a combination thereof.

[0088] Binder

[0089] The binder improves the bonding properties between the positive electrode active material particles and the bonding properties between the positive electrode active material particles and the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin and nylon, but are not limited thereto.

[0090] Conductive Materials

[0091] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material may be used as the conductive material (e.g., conductive material) unless it causes chemical changes (e.g., undesirable chemical changes in a rechargeable lithium battery). Examples of the conductive material may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers (e.g., conductive polymers) such as polyphenylene derivatives; or mixtures thereof.

[0092] The binder and the conductive material may be contained in an amount of about 0.5 wt % to about 5 wt % based on 100 wt % of the positive electrode active material layer, respectively.

[0093] The positive electrode current collector may include Al foil, but is not limited thereto.

[0094] Rechargeable lithium battery

[0095] Some embodiments provide a rechargeable lithium battery comprising the aforementioned positive electrode, negative electrode and electrolyte. The aforementioned positive electrode active material can be applied not only to lithium ion batteries, but also to all-solid-state rechargeable batteries. Accordingly, in some embodiments, the rechargeable lithium battery comprises a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, and in some embodiments, the all-solid-state rechargeable battery comprises a positive electrode, a negative electrode and a solid electrolyte layer between the positive electrode and the negative electrode. In the following, for convenience, the configuration of a lithium ion battery using an electrolyte is explained in more detail.

[0096] Depending on the shape, the rechargeable lithium batteries may be classified into a cylindrical type, a prismatic type, a pouch type, a coin type, etc. Figure 1 to Figure 4 A schematic diagram for explaining a rechargeable lithium battery according to an embodiment. Figure 1 A cylindrical battery is shown, Figure 2 A prismatic cell is shown, and Figure 3 and Figure 4 Pouch cell shown. Figure 1 to Figure 4 , the rechargeable lithium battery 100 includes an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is accommodated. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte. Figure 1 As shown in , the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 2 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3 and Figure 4 As shown in FIG. 1 , the rechargeable lithium battery 100 includes an electrode tab 70 ( Figure 4 ), for example, the positive electrode terminal tab 71 and the negative electrode terminal tab 72 ( Figure 3 ), which serve as an electrical path for guiding the current formed in the electrode assembly 40 to the outside.

[0097] Negative electrode

[0098] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and the negative electrode active material layer may include a negative electrode active material, a binder, a conductive material (eg, an electrically conductive material), or a combination thereof.

[0099] Negative electrode active material

[0100] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, and / or a transition metal oxide.

[0101] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbonaceous negative electrode active material. The crystalline carbon may be irregular and / or flaky, flaky, spherical, and / or fibrous natural graphite and / or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.

[0102] Lithium metal alloys include alloys of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0103] The material capable of being doped / undoped with lithium may be a Si-based negative electrode active material and / or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0<x≤2), Si-Q alloy (wherein Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po and combinations thereof) or combinations thereof. The Sn-based negative electrode active material may be Sn, SnO2, a Sn alloy or a combination thereof.

[0104] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) may be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it may include secondary particles (cores) in which silicon primary particles are aggregated and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon may also be present between silicon primary particles, for example, silicon primary particles may be coated with amorphous carbon. Secondary particles may be dispersed in an amorphous carbon matrix.

[0105] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.

[0106] When the silicon-carbon composite includes silicon and amorphous carbon, the content of silicon may be about 10 wt % to about 50 wt %, and the content of amorphous carbon may be about 50 wt % to about 90 wt % based on 100 wt % of the silicon-carbon composite. In some embodiments, when the composite includes silicon, amorphous carbon and crystalline carbon, the content of silicon may be about 10 wt % to about 50 wt %, the content of crystalline carbon may be about 10 wt % to about 70 wt %, and the content of amorphous carbon may be about 20 wt % to about 40 wt % based on 100 wt % of the silicon-carbon composite.

[0107] In some embodiments, the thickness of the amorphous carbon coating layer may be about 5 nm to about 100 nm. The average particle size (D 50 ) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as silicon alone, in the form of a silicon alloy and / or in an oxidized form. The oxidized form of silicon may be SiO x (0<x≤2) indicates. At this time, the atomic content ratio of Si:O indicating the degree of oxidation may be about 99:1 to about 33:67. As used herein, when no definition is provided otherwise, the average particle size (D 50 ) indicates the diameter of the particles where the cumulative volume in the particle distribution is about 50 volume %.

[0108] The Si-based negative electrode active material and / or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material and / or the Sn-based negative electrode active material are mixed with the carbon-based negative electrode active material and used, the mixing ratio may be about 1:99 to about 90:10 by weight.

[0109] Binder

[0110] The binder is used to bind the negative electrode active material particles well to each other and also to bind the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder or a combination thereof.

[0111] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0112] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol or a combination thereof.

[0113] When the aqueous binder is used as the negative electrode binder, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and an alkali metal salt thereof may be mixed together and used. The alkali metal may be Na, K and / or Li.

[0114] The dry binder may be a polymer material capable of becoming fibers (eg, capable of being fibrillized or fiberized), and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0115] Conductive Materials

[0116] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material may be used as the conductive material (e.g., conductive material) unless it causes chemical changes (e.g., undesirable chemical changes in a rechargeable lithium battery). Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum silver, etc.; conductive polymers (e.g., conductive polymers) such as polyphenylene derivatives; or mixtures thereof.

[0117] Based on 100wt% of the negative electrode active material layer, the content of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on 100wt% of the negative electrode active material layer, the content of the binder may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0.5wt% to about 5wt% of the conductive material.

[0118] current collector

[0119] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) and / or alloys thereof, and may be in the form of foil, sheet and / or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.

[0120] Electrolytes

[0121] For example, the electrolyte for a rechargeable lithium battery may be an electrolyte that may include a non-aqueous organic solvent and a lithium salt.

[0122] The non-aqueous organic solvent is used as a medium for transmitting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent can be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent or a combination thereof.

[0123] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In some embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, which includes a double bond, an aromatic ring and / or an ether bond, etc.); amides such as dimethylformamide; dioxolanes (such as 1,3-dioxolane 1,4-dioxolane, etc.); cyclopentane sulfone, etc.

[0124] The non-aqueous organic solvent may be used alone or in a mixture of two or more types (or species), and when two or more types (or species) are used in a mixture, the mixing ratio may be appropriately or properly adjusted according to the appropriate or desired battery performance, which should be readily apparent to those skilled in the art after reading this disclosure.

[0125] When the carbonate-based solvent is used, the cyclic carbonate and the chain carbonate may be mixed together and used, and the cyclic carbonate and the chain carbonate may be mixed together in a volume ratio of about 1:1 to about 1:9.

[0126] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed together in a volume ratio of about 1:1 to about 30:1 and used.

[0127] The electrolyte may further include vinyl ethylene carbonate, vinylene carbonate and / or ethylene carbonate-based compounds to improve the battery cycle life.

[0128] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0129] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the battery, enables the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB) and lithium bis(oxalato)borate (LiBOB).

[0130] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate or proper ion conductivity and viscosity, so that excellent performance may be achieved and lithium ions may be efficiently transferred.

[0131] Diaphragm

[0132] Depending on the type (or kind) of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).

[0133] The separator may include a porous substrate and a coating on one or both surfaces of the porous substrate, the coating including an organic material, an inorganic material, or a combination thereof.

[0134] The porous substrate can be a polymer film formed from: any one selected from the group consisting of polymer polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, fiberglass, TEFLON, and polytetrafluoroethylene, and / or copolymers and / or mixtures of two or more thereof.

[0135] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0136] The organic material may include a (meth)acryl-based copolymer including a first structural unit derived from (meth)acrylamide, and a second structural unit including at least one selected from a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof.

[0137] The inorganic material may include inorganic particles selected from the group consisting of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.

[0138] The organic material and the inorganic material may be mixed together in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.

[0139] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.

[0140] Examples and comparative examples of the present disclosure are described below. However, the following examples are merely examples of embodiments of the present disclosure, and the present disclosure is not limited to the following examples.

[0141] Example 1

[0142] 1. Preparation of positive electrode active material

[0143] (1) Preparation of precursor

[0144] A mixed solution of metal raw materials was prepared by dissolving nickel sulfate (NiSO4·6H2O) and manganese sulfate (MnSO4·H2O) in distilled water at a molar ratio of Ni:Mn = 50:50. In order to form a complex compound, ammonia water (NH4OH) was prepared as a complexing agent and sodium hydroxide (NaOH) as a precipitating agent.

[0145] After adding ammonia water at a concentration of 0.25 M into the reactor, the reactor was heated at 50 °C at a rate of 142 ml / min and 34 ml / min and 3.0 kW / m 3 The metal raw material mixed solution and the complexing agent were injected into the mixture with a stirring power of 1000 ℃ to start the reaction. When NaOH was injected into the mixture to maintain the pH, the reaction was carried out for 30 hours. When the average size of the obtained particles reached about 10.5 μm, the reaction was terminated. The obtained material was washed and dried with hot air at about 150° C. for 24 hours to obtain a nickel-manganese composite hydroxide (Ni 0.5 Mn 0.5 (OH)2).

[0146] (2) Preparation of positive electrode active material

[0147] Ni 0.5 Mn 0.5 (OH)2 and LiOH were mixed together in a molar ratio of Li / (Ni+Mn)=1.3, and then heat-treated by increasing the temperature at 5°C / min and maintaining it at 950°C in an oxygen atmosphere, and cooling to room temperature at 5°C / min for a total of 24 hours to prepare 0.3[Li 1.13 Ni 0.44 Mn 0.44 O2]+0.7[0.61(LiNi 0.72 Mn 0.28 O2)+0.26(Li2MnO3)] positive electrode active material.

[0148] 2. Manufacturing of rechargeable lithium battery cells (half-cells)

[0149] 97.7 wt% of the positive electrode active material, 1.2 wt% of the polyvinylidene fluoride binder and 1.1 wt% of the carbon nanotube conductive material were mixed together to prepare a positive electrode active material layer slurry, and the slurry was coated on an aluminum foil current collector, and then dried and pressed to make a positive electrode. In this paper, the loading level of the positive electrode active material layer was 10 mg / cm 2 , and the density of the final rolled positive electrode was about 3.5 g / cc.

[0150] A rechargeable lithium battery cell was manufactured by an existing method using a lithium counter electrode as a negative electrode, a polytetrafluoroethylene separator, and an electrolyte solution including 1M LiPF6 and 1.5wt% vinylene carbonate dissolved in a solvent in which ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate were mixed together in a volume ratio of 2:4:4.

[0151] Example 2

[0152] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the positive electrode active material precursor was prepared by changing the molar ratio of Ni to Mn to 66:34. The positive electrode active material of Example 2 can be expressed as 0.15 [Li 1.13 Ni 0.57 Mn 0.30 O2]+0.85[0.61(LiNi 0.94 Mn 0.06 O2)+0.26(Li2MnO3)].

[0153] Example 3

[0154] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by changing the molar ratio of Li / (Ni+Mn) to 1.2. The positive electrode active material of Example 3 can be expressed as 0.41[Li 1.09 Ni 0.46 Mn 0.46 O2]+0.59[0.85(LiNi 0.56 Mn 0.44 O2)+0.10(Li2MnO3)].

[0155] Example 4

[0156] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by changing the molar ratio of Li / (Ni+Mn) to 1.1. The positive electrode active material of Example 4 can be expressed as 0.43[Li 1.05 Ni 0.48 Mn 0.48 O2]+0.57[0.85(LiNi 0.56 Mn 0.44 O2)+0.10(Li2MnO3)].

[0157] Comparative Example 1

[0158] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the positive electrode active material precursor was prepared by changing the molar ratio of Ni to Mn to 34:66. The positive electrode active material of Comparative Example 1 can be expressed as 0.66 (LiNi 0.50 Mn 0.50 O2)+0.34(Li2MnO3).

[0159] Comparative Example 2

[0160] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the positive electrode active material precursor was prepared by changing the molar ratio of Ni to Mn to 40:60. The positive electrode active material of Comparative Example 2 can be expressed as 0.70 (LiNi 0.57 Mn 0.43 O2)+0.30(Li2MnO3).

[0161] Comparative Example 3

[0162] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the positive electrode active material precursor was prepared by changing the molar ratio of Ni to Mn to 75:25. The positive electrode active material of Comparative Example 3 can be expressed as 0.75·LiNiO2+0.25(Li2MnO3).

[0163] Comparative Example 4

[0164] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the positive electrode active material precursor was prepared by changing the molar ratio of Ni to Mn to 80:20. The positive electrode active material of Comparative Example 4 can be expressed as 0.80·LiNiO2+0.20(Li2MnO3)+0.05Li2O.

[0165] Example 5

[0166] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 2, except that the heat treatment temperature was changed to 700°C.

[0167] Comparative Example 5

[0168] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 2, except that the heat treatment temperature was changed to 500°C.

[0169] To facilitate understanding, each designed content of the positive electrode active material of Example 1 and Example 2 and Comparative Examples 1 to 4 is briefly shown in Table 1, wherein the contents of Example 1, Example 3 and Example 4 are shown in Table 2, and the contents of Example 2, Example 5 and Comparative Example 5 are shown in Table 3.

[0170] Table 1

[0171]

[0172] Table 2

[0173]

[0174] Table 3

[0175]

[0176] Evaluation Example 1: XRD and SEM evaluation

[0177] X-ray diffraction analysis was performed using Bruker's Powder XRD (D8 Advance) equipment under the following conditions.

[0178] -X-ray wavelength: (CuKα1)

[0179] – Slit conditions: divergence slit 0.5°, scattering slit 0.5°, receiving slit 0.20mm

[0180] – Scanning conditions: continuous scanning, 10°≤2θ≤80°, 0.01° / step, 1.27° / min, total measurement time 55 min.

[0181] After performing XRD analysis on the positive electrode active materials of the examples and comparative examples, the peak intensity (I a ) corresponds to Space group LiNi z Mn 1-z The peak intensity of the (003) plane of O2 (I b ) ratio, and the results are shown in Tables 1 to 3 as I a / I b In addition, the lattice constant a The ratio c / a of the lattice constant c to the lattice constant a is shown in Tables 1 and 2.

[0182] Referring to Tables 1 to 3, the positive electrode active materials of the embodiments satisfy an I a / I bRatio. Comparative Example 1 and Comparative Example 2, in which the nickel content is less than 50 mol%, satisfy the requirement of greater than 2%. a / I b As shown in Table 2, as the molar ratio of lithium to total metal excluding lithium decreases from 1.3 to 1.1, I a / I b The ratio decreases, and the ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material also decreases, and the voltage drop trend also decreases as the average discharge voltage increases.

[0183] On the other hand, the XRD analysis curves of the positive electrode active materials of Example 2, Example 5 and Comparative Example 5 are shown in Figure 5 In. Figure 5 In the figure, the horizontal axis means 2θ (°). In this article, the large curve graph represents the peak on the (003) plane, and the small curve graph represents the peak on the (020) plane. Figure 5 As shown in Table 3, even if materials having the same composition are applied, as the heat treatment temperature during synthesis increases, the peak intensity of the (003) plane becomes stronger, but the peak intensity of the (020) plane becomes weaker, and thus, I a / I b The proportion gradually decreases. Figure 6 to Figure 8 SEM images of the particle surfaces of the positive electrode active materials of Example 2, Example 5 and Comparative Example 5 are shown in order. Figure 6 to Figure 8 , depending on the heat treatment temperature, the particles each have a different shape.

[0184] In addition, these embodiments satisfy greater than or equal to or greater than or equal to , and at the same time (e.g., synchronously), the ratio of the c lattice constant to the a lattice constant (c / a) is less than or equal to 4.968. As in the embodiment, when the a lattice constant is greater than or equal to And when the c / a ratio is less than or equal to 4.968, the ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material decreases, the average discharge voltage increases, and the voltage drop trend decreases.

[0185] Evaluation Example 2: Powder compaction density

[0186] Each of the positive electrode active materials of Examples 1 to 4 and Comparative Examples 1 to 4 was pressed into a compact at a pressure of 3.3 tons, its density was measured, and the results are shown as P / D (powder compaction density) in Tables 1 and 2. Referring to Tables 1 and 2, the positive electrode active materials of the Examples have a powder compaction density greater than 2.70 g / cc, which is ultimately higher than the powder compaction density of Comparative Examples 1 and 2, which have a high ratio of capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material due to the high manganese content. Referring to Table 2, as the molar ratio of lithium to the total metal excluding lithium decreases from 1.3 to 1.1, the powder compaction density ultimately increases. Comparative Examples 3 and 4, which have low manganese contents, exhibit higher powder compaction densities than the Examples, but since the ratio of the additional capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material is less than or equal to 0, it is difficult to achieve high capacity. Accordingly, the positive electrode active material of the embodiment achieves additional capacity expressed by O-redox and simultaneously (eg, simultaneously) has a powder compaction density greater than 2.70 g / cc, resulting in a much higher electrode density.

[0187] Since the basic materials LiNiO2, LiMnO2, and Li2MnO3 of the positive electrode active material have theoretical densities of 4.62 g / cc, 4.04 g / cc, and 3.73 g / cc, respectively, the lithium-rich manganese material (such as the positive electrode active material of some embodiments) tends to have a lower theoretical density as the Mn ratio increases, but the theoretical density increases as the Ni ratio increases. However, as described above, because O-redox is expressed by Li2MnO3, O-redox for achieving high capacity conversely reduces the theoretical density, thereby offsetting the effect of increasing capacity. In this regard, the materials of Example 1 and Example 2 have a high Mn and low Ni ratio than Comparative Example 1 and Comparative Example 2, which have a high ratio of capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material, and thus exhibit a high theoretical density, but have a high Mn ratio than Comparative Example 3 and Comparative Example 4, and thus exhibit a low theoretical density, but achieve a high capacity due to the expression of O-redox, wherein a strategy of finding a balance between appropriate or proper O-redox expression and theoretical density is applied. In addition, as further described below, at the same Ni and Mn ratio, as the Li / Me ratio (i.e., the molar ratio of lithium to the total metal excluding lithium) decreases, because the amount of the material Li2MnO3 expressing O-redox decreases, there is an effect of increasing the theoretical density and simultaneously (e.g., synchronously) limiting the O-redox expression, which is consistent with the results of Example 3 and Example 4, and accordingly, this strategy is another effective way to find a balance between capacity control expressed by O-redox and improvement in theoretical density.

[0188] Evaluation Example 3: Residual Lithium

[0189] The residual lithium content on the surface of the positive electrode active materials of Examples 1 to 4 and Comparative Examples 1 to 4 was measured by HCl titration, and the results are shown in Tables 1 and 2. In the table, the residual lithium content measured by using the unit of ppm is 10 based on 100 wt % of each positive electrode active material. -4 wt%. Specifically, 10 g of the positive electrode active material was added to 100 ml of distilled water, then stirred at 300 rpm for 30 minutes, and then the pH change was measured while HCl was added thereto. In this paper, since the unreacted residual lithium on the surface of the positive electrode active material appears in the presence of Li2CO3, LiOH, etc., the H + The reaction is used to titrate CO3 2- OH - ions, etc. The amount of the HCl solution added above is used to calculate the residual lithium content. Referring to Tables 1 and 2, the positive electrode active materials of the embodiments have a residual lithium content of less than or equal to about 0.4wt% or less than or equal to about 0.3wt% or less than or equal to about 0.1wt%. In contrast, Comparative Examples 3 and 4, which have a nickel content greater than 70mol%, have a residual lithium content greater than 0.4wt%.

[0190] Evaluation Example 4: Capacity Evaluation Expressed by O-Redox

[0191] The half-cells of Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged as in the first setting described above, and the discharge capacity (X) of the second cycle is provided as "discharge capacity" in Tables 1 and 2. Separately, the half-cells were charged and discharged twice as in the second setting to measure the discharge capacity (Y) at the second cycle. The "ΔC" obtained by subtracting Y from X is shown in Tables 1 and 2, and means the capacity expressed by O-redox. {(XY) / X}×100 is calculated and then shown as "ΔC / C" in Tables 1 and 2. tot ”, and means the ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material. Referring to Tables 1 and 2, the embodiments have a ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material of less than 15%. In Table 1, Comparative Examples 1 and 2 show a high ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material of greater than or equal to 19.6%, and Comparative Examples 3 and 4 do not show the capacity expressed by O-redox. Referring to Table 2, as the molar ratio of lithium to the total metal excluding lithium changes from 1.3 to 1.1, the ratio of the capacity expressed by O-redox to 100% of the total capacity of the positive electrode active material decreases more.

[0192] Evaluation Example 5: Evaluation of reversible discharge capacity ratio

[0193] In the capacity evaluation method expressed by O-redox of Evaluation Example 4, the charge capacity of the first cycle of the first setting was divided by the discharge capacity of the second cycle of the first setting, and the results were shown as a reversible discharge capacity ratio in Tables 1 and 2. Referring to Table 2, Examples 3 and 4, in which the molar ratio of lithium to the total metal excluding lithium was reduced to less than or equal to 1.2, showed an improved reversible discharge capacity ratio of greater than or equal to 77%, and it can be confirmed that these examples were prepared as optimized or improved materials for achieving high energy density.

[0194] Evaluation Example 6: Evaluation of average discharge voltage

[0195] The half-cells of Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged as in the first setting, and the average discharge voltage at the second cycle was measured, and the results are shown as "average voltage" in Tables 1 and 2. The average discharge voltage was obtained by obtaining a discharge voltage curve (voltage-capacity curve graph) after charging and discharging the half-cell, integrating the area under the curve, and dividing the area by the discharge capacity.

[0196] Referring to Tables 1 and 2, Comparative Examples 1 and 2 exhibited an average discharge voltage less than or equal to 3.801 V, but the embodiment exhibited an improved average discharge voltage greater than or equal to 3.83 V. Referring to Table 2, as the molar ratio of lithium to total metal excluding lithium decreased from 1.3 to 1.1, the average discharge voltage increased.

[0197] Evaluation Example 7: Evaluation of cycle life characteristics and voltage drop characteristics

[0198] The half-cells of Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged as in the first setting, and then charged and discharged 50 times or more at 1.0C in a voltage range of 3.0V to 4.45V at 45°C to calculate the ratio of the 50th cycle discharge capacity to the initial discharge capacity (i.e., the capacity retention rate at the 50th cycle), which is shown as "high temperature cycle life" in Tables 1 and 2. In addition, after subtracting the average discharge voltage at the 50th cycle from the average discharge voltage at the first cycle at 1.0C, the results are shown as "voltage drop" in Tables 1 and 2.

[0199] Referring to Tables 1 and 2, Comparative Examples 3 and 4 exhibit degraded cycle life characteristics, i.e., the capacity retention rate at the 50th cycle is less than or equal to 71%, but the embodiment achieves a cycle life characteristic of greater than or equal to 77% or greater than or equal to 94%. In addition, Comparative Examples 1 and 2 exhibit a voltage drop greater than or equal to 90 mV, but the embodiment exhibits a reduced voltage drop of less than or equal to 70 mV.

[0200] Although the subject matter of the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it is to be understood that the present disclosure is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.

Claims

1. A positive electrode active material for a rechargeable lithium battery, comprising a compound represented by Chemical Formula 1: [Chemical formula 1] a[Li 1+x (Ni y Mr 1-y ) 1-x O2]+(1-a)[b(LiNi z Mr 1-z O2)+c(Li2MnO3)] in, In Chemical Formula 1, 0<a<1, 0.03≤x≤0.2, 0.35≤y≤0.7, 0<b<1, 0<c<1, and 0.5≤z≤1.

0.

2. The positive electrode active material according to claim 1, wherein: The positive electrode active material includes the following two: By [Li 1+x (Ni y Mn 1-y ) 1-x O2] represented by the solid solution phase, and By [b(LiNi z Mn 1-z O2)+c(Li2MnO3)] represented by the composite phase.

3. The positive electrode active material according to claim 1, wherein: In Chemical Formula 1, 0.5≤y≤0.66, 0.5≤z≤0.

95.

4. The positive electrode active material according to claim 1, wherein: In Chemical Formula 1, 0.03≤x≤0.15, and / or 0.1≤a≤0.9, 0.1≤b≤0.9, and 0.1≤c≤0.

9.

5. The positive electrode active material according to claim 1, wherein: The capacity due to oxygen redox is Li 1+x (Ni y Mn 1-y ) 1-x O2 and / or Li2MnO3 expression.

6. The positive electrode active material according to claim 1, wherein: The capacity expressed by oxygen redox accounts for less than 15% of the total capacity of 100% of the positive electrode active material.

7. The positive electrode active material according to claim 6, wherein: Using Equation 1, calculate the ratio of the capacity expressed by oxygen redox to 100% of the total capacity of the positive electrode active material: Equation 1 {(XY) / X}×100 Wherein, in Equation 1, X is the discharge capacity of the second cycle of the first setting, and Y is the discharge capacity of the second cycle of the second setting, wherein the first setting and the second setting refer to manufacturing a half-cell using a positive electrode and charging and discharging under the following conditions, the positive electrode active material is applied to the positive electrode, and the second setting is performed immediately after the first setting, First Setup (1) First cycle: charging at 25°C at a constant current of 0.1C to 4.55V-4.8V, then maintaining the voltage until the current value reaches 0.05C, then discharging at a constant current of 0.1C to 2.5V, and (2) Second cycle: Charge to 4.45 V at 25°C with a constant current of 0.2C, then maintain this voltage until the current value reaches 0.05C, then discharge to 2.5 V at a constant current of 0.2C, Second Setting (1) First cycle: charging to 4.45 V at 25°C at a constant current of 0.2C, then maintaining this voltage until the current value reaches 0.05C, then discharging to 2.5 V at a constant current of 0.2C, and (2) Second cycle: Charge to 4.45 V at 25°C at a constant current of 0.2C, then maintain the voltage until the current value reaches 0.05C, and then discharge to 2.5 V at a constant current of 0.2C.

8. The positive electrode active material according to claim 1, wherein: The positive electrode active material has an average discharge voltage greater than or equal to 3.83V (vs.Li / Li+) , and / or in: In the X-ray diffraction analysis of the positive electrode active material, the peak intensity corresponding to the 020 plane of Li2MnO3 of the C2 / m space group accounts for Space group LiNi z Mn 1-z The ratio of the peak intensity of the 003 plane of O2 is less than or equal to 2%.

9. The positive electrode active material according to claim 1, wherein: The reversible discharge capacity ratio calculated by Equation 2 is greater than or equal to 72%: Equation 2 (X / A)×100 Wherein, in Equation 2, A is the charge capacity of the first cycle of the first setting, X is the discharge capacity of the second cycle of the first setting, and the first setting refers to manufacturing a half-cell using a positive electrode and charging and discharging under the following conditions, the positive electrode active material is applied to the positive electrode, First Setup (1) First cycle: charging at 25°C at a constant current of 0.1C to 4.55V-4.8V, then maintaining the voltage until the current value reaches 0.05C, then discharging at a constant current of 0.1C to 2.5V, and (2) Second cycle: Charge to 4.45 V at 25°C at a constant current of 0.2C, then maintain the voltage until the current value reaches 0.05C, and then discharge to 2.5 V at a constant current of 0.2C.

10. The positive electrode active material according to claim 9, wherein: The upper limit voltage of the first cycle of the first setting is 4.65V.

11. The positive electrode active material according to claim 9, wherein: The reversible discharge capacity ratio is greater than or equal to 77%.

12. The positive electrode active material according to claim 1, wherein: The positive electrode active material has a powder compaction density greater than 2.70 g / cc.

13. The positive electrode active material according to claim 1, wherein: The positive electrode active material has a powder compaction density of 2.71 g / cc to 2.85 g / cc.

14. The positive electrode active material according to claim 1, wherein: (i) the residual lithium content on the surface of the positive electrode active material is less than or equal to 0.4 wt %; and / or (ii) the residual lithium content on the surface of the positive electrode active material is less than or equal to 0.1 wt %; and / or (iii) the lattice constant a in X-ray diffraction analysis of the positive electrode active material is greater than or equal to and / or (iv) the lattice constant a in X-ray diffraction analysis of the positive electrode active material is greater than or equal to and / or (v) The ratio of the c lattice constant to the a lattice constant in X-ray diffraction analysis of the positive electrode active material is less than or equal to 4.

968.

15. A method for preparing a positive electrode active material, comprising: The precursor represented by Chemical Formula 2 and the lithium raw material are mixed together and heat-treated, The molar ratio of lithium in the lithium raw material to the total metal of the precursor satisfies 1.06 to 1.5: Chemical formula 2 No y2 Mn 1-y2 (OH)2 In the chemical formula 2, 0.5≤y2≤0.

7.

16. The method of claim 15, wherein: The heat treatment is performed at a temperature range of 700° C. to 1100° C. for 10 to 40 hours.

17. The method of claim 15, wherein: The heat treatment includes a temperature increasing step, a temperature maintaining step and a temperature decreasing step, and The temperature increase rate in the temperature increase step and the temperature decrease rate in the temperature decrease step are 1° C. / min to 10° C. / min, respectively.

18. A positive electrode for a rechargeable lithium battery, comprising: The positive electrode active material according to any one of claims 1 to 14 or a positive electrode active material prepared by the method according to any one of claims 15 to 17.

19. A rechargeable lithium battery comprising: The positive electrode according to claim 18, Negative electrode, a separator between the positive electrode and the negative electrode, and Electrolytes.

20. An all-solid-state rechargeable battery comprising: The positive electrode according to claim 18, negative electrode, and A solid electrolyte layer is between the positive electrode and the negative electrode.